The Black Death - Griffin, Mary, 1978- (Look at world history., 2020)
Briefly explores the history of the Black Death and plague epidemic that hit Europe during the 1300s. Discusses what we now know to be the cause of the plague and how and why it spread and became so deadly around the world in the Middle Ages. Includes a glossary.